2015
DOI: 10.1177/2156587215580882
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Online Training in Mind–Body Skills?

Abstract: Online elective training offers a feasible strategy to improve mindfulness, stress, and confidence in providing calm, compassionate care. Additional studies are needed to determine the impact of required versus elective courses, the optimal dosage and content of training, and the costs and benefits of online versus in-person training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 60 publications
3
60
0
1
Order By: Relevance
“…However, as this online MBT program was shown to decrease stress, increase adaptive coping strategies, increase emotional intelligence, and enhance resilience, additional research comparing the online with the offline approach is needed. Additionally, other online training programs and interventions designed to teach mind–body skills have been reported to affect stress, mindfulness, resilience, empathy, anxiety, and depression [ 7 8 , 49 ]. Thus, we should develop and study effective online training and intervention programs for mind and body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as this online MBT program was shown to decrease stress, increase adaptive coping strategies, increase emotional intelligence, and enhance resilience, additional research comparing the online with the offline approach is needed. Additionally, other online training programs and interventions designed to teach mind–body skills have been reported to affect stress, mindfulness, resilience, empathy, anxiety, and depression [ 7 8 , 49 ]. Thus, we should develop and study effective online training and intervention programs for mind and body.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet offers many advantages as a medium for easy participation in MBT and is not subject to the limitations of time and space that are inherent to traditional group training. There is evidence of the impact of online training in mind–body skills in terms of significant improvements related to stress, mindfulness, and participants’ confidence in their ability to provide calm and compassionate care, with emphasis on the cost-effectiveness and convenience of online programs [ 7 ]. The same researchers have also reported effects of online mind–body skills training on resilience, mindfulness, and empathy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two studies were discarded due to full-text unavailability. Detailed full-text examination of 24 remaining studies revealed that 18 did not meet inclusion criteria (Kemper et al, 2015, Krusche et al, 2013, Ljotsson et al, 2011, Murray et al, 2015, Zernicke et al, 2013), for example, Michel et al measured strain-based work-family conflict, but had no direct measure of perceived-stress (Michel et al, 2014). Scanning reference lists of the remaining six studies identified one additional eligible study (Wolever et al, 2012), with yet another identified by hand-searching contents pages from two journals (Mak et al, 2015).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…We are particularly encouraged with the attention now given to educational programs designed to develop resilience, empathy, selfcompassion, and mindfulness. These efforts include: mindfulness training, presented through workshops 11 and/ or online modules 12 ; CREW (Civility, Respect, and Engagement at Work) training to develop better civility and communication and to mitigate burnout in the workplace 13 ; and comprehensive wellness curricula such as the University of Arizona's Pediatric Integrative Medicine in Residency Curriculum 14 and the American Academy of Pediatrics' Resilience in the Face of Grief and Loss Resident Curriculum that focus on developing important cognitive and emotional skills of pediatric trainees to help them provide high-quality care while fostering their personal wellness and resilience. 15 The Pediatric Residency Burnout-Resilience Study Consortium (www.…”
Section: The Call For Better Systems Personal-social Skills Developmmentioning
confidence: 99%